On Neighborhoods of Analytic Function Subclasses Associated with the q-Ruscheweyh Operator - Eljamal, Ebtisam. A; Amhalhil, Jaffalah J; Aldweby, Huda; Alawiss, Najla J; Abosetta, Mariam R (المجلة العلمية لكلية التربية, 2025)
This Abstract: In this present, we extend the notion of neighborhoods in families of analytic functions using q-derivative . A systematic study of inclusion relationships among (m, δ, q)-neighborhoods of canonically normalized analytic functions with negative coefficients is presented